2020
DOI: 10.21037/qims-19-723
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced magnetic resonance (MR) T1 mapping with low-dose gadolinium-diethylenetriamine pentaacetic acid (Gd-DTPA) is promising in identifying clear cell renal cell carcinoma histopathological grade and differentiating fat-poor angiomyolipoma

Abstract: Background: This study aimed to identify clear cell renal cell carcinoma (ccRCC) histopathological grade and differentiate it from fat-poor angiomyolipoma (AML). This was achieved through contrastenhanced magnetic resonance (MR) T1 mapping with intravenous low-dose gadolinium-diethylenetriamine pentaacetic acid (Gd-DTPA).Methods: In total, 56 consecutive patients received MR scanning between January 2016 and December 2018 using the pre-and post-contrast-enhanced T1 mapping sequences with low-dose Gd-DTPA (0.03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
(47 reference statements)
1
17
1
Order By: Relevance
“…Studies of hepatocellular carcinoma and clear cell renal cell carcinoma have similarly shown that high-grade tumors, presented as a high degree of malignancy, have higher native T1 values. 12,13,38 However, the result was different from the study of Wu et al, 22 in which ADC values were positively correlated with native T1 values in the assessment of myocardial fibrosis in hypertrophic cardiomyopathy patients. This may be because the high water content of inflammatory and fibrotic tissues leads to high ADC and T1 values.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Studies of hepatocellular carcinoma and clear cell renal cell carcinoma have similarly shown that high-grade tumors, presented as a high degree of malignancy, have higher native T1 values. 12,13,38 However, the result was different from the study of Wu et al, 22 in which ADC values were positively correlated with native T1 values in the assessment of myocardial fibrosis in hypertrophic cardiomyopathy patients. This may be because the high water content of inflammatory and fibrotic tissues leads to high ADC and T1 values.…”
Section: Discussioncontrasting
confidence: 62%
“…In this study, the T1 values of patients with SCLC were significantly higher than those of patients with NSCLC; thus, T1 values may also potentially distinguish between SCLC and NSCLC. The possible reasons may be that higher degrees of micronecrosis and incomplete necrosis may occur in SCLC because of rapid growth, which is below the spatial resolution of MRI and is therefore difficult to exclude in ROI delineation 12,13,25 . Meanwhile, SCLC is characterized by poor adhesion, loose nests, and infiltration along the intercellular space, inducing more extracellular matrix (ECM), and, thus, yielding larger T1 values 12,25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT diagnosis is superior to percutaneous biopsy because of its noninvasiveness; however, it is inferior in terms of diagnostic accuracy (20,21). Novel imaging techniques, such as magnetic resonance imaging (MRI) and dual-energy spectral CT, are capable to assess the grading level of CCRCC, however, their predictive performance do not match that of percutaneous biopsy, and the diagnostic results depend on the experience of radiologists (22)(23)(24). By quantifying tumor heterogeneity through the spatial arrangement of image voxels with signal-intensity variations and detecting the imperceptible differences of the intensity distribution in medical images, CT radiomics can noninvasively predict the pathological grade of tumors with satisfactory performance (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, relaxometry characteristics have been investigated in several brain imaging studies (11)(12)(13)(14). Relaxometry studies have also been conducted on other organs, such as the cartilage (15), kidney (16), etc. However, the application of relaxometry in clinical practice is limited by several factors.…”
Section: Introductionmentioning
confidence: 99%